Terapi Mindfulness pada Ibu Hamil Hipertensi di Wilayah Puskesmas Pajarakan Probolinggo - Mariani Mariani; Dodik Hartono (Lembaga Pengembangan Kinerja Dosen, 2023)
High blood pressure during pregnancy is a disease that often threatens pregnancy. This condition causes several factors for the fetus such as (fetal growth is also hampered in the womb, stillbirth in the womb, premature birth). Hypertension is a dangerous disease, especially if it occurs in pregnant women, so it needs special treatment because it can reduce blood flow to the placenta, which will affect the supply of oxygen and nutrients to the baby. The aim of this community service is to help lower the blood pressure of pregnant women with hypertension through the application of Mindfulness therapy. The methods used are health education and demonstrations of mindfulness based on breathing exercises. The results of this community service activity were that pregnant women's knowledge about mindfulness therapy increased from 14% to 88%, participants were able to demonstrate mindfulness therapy well by 91% and pregnant women's blood pressure decreased by 86.38%.